2017
DOI: 10.1590/18069657rbcs20160558
|View full text |Cite
|
Sign up to set email alerts
|

Weathering of Rhyolites and Soil Formation in an Atlantic Forest Fragment in Northeastern Brazil

Abstract: Weathering and pedogenesis have been studied for a wide range of rocks and climates around the world. However, the eruption of rhyolitic magmas is a rare geological event, which leads to few studies associated with the rhyolite-soil-landscape relationship. In this context, this study evaluated the influence of rhyolite weathering on the properties of soils along a slope in an Atlantic Forest environment in the state of Pernambuco, northeastern Brazil. Four weathering profiles derived from rhyolites were classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(35 reference statements)
1
3
0
1
Order By: Relevance
“…Other soils with Bt horizons are common in this region (Brasil, 1972) with chemical and mineralogical properties similar to those of the studied soils, such as the Argissolos Vermelho-Amarelos developed from the Cabo Basin rhyolites (Brilhante et al, 2017); these authors also described Cambissolo in this region. Argissolos Vermelho-Amarelos is typical of the PE coastal humid region in an area of pre-Cambrian rocks corresponding to the crystalline basement (Lima et al, 2008) and presents properties similar to those observed in the present study (mainly P1 and P2), such as base poverty, a clay fraction consisting mainly of 1:1 phyllosilicates and oxides, and being practically devoid of mineral reserves to release plant nutrients.…”
Section: Relation Of Soil To the Adjacent Environmentsupporting
confidence: 62%
See 1 more Smart Citation
“…Other soils with Bt horizons are common in this region (Brasil, 1972) with chemical and mineralogical properties similar to those of the studied soils, such as the Argissolos Vermelho-Amarelos developed from the Cabo Basin rhyolites (Brilhante et al, 2017); these authors also described Cambissolo in this region. Argissolos Vermelho-Amarelos is typical of the PE coastal humid region in an area of pre-Cambrian rocks corresponding to the crystalline basement (Lima et al, 2008) and presents properties similar to those observed in the present study (mainly P1 and P2), such as base poverty, a clay fraction consisting mainly of 1:1 phyllosilicates and oxides, and being practically devoid of mineral reserves to release plant nutrients.…”
Section: Relation Of Soil To the Adjacent Environmentsupporting
confidence: 62%
“…The southern coast of Pernambuco is inserted in areas of dissected plateaus. In addition to the close relationship between parent material and soil properties (Brilhante et al, 2017;Neves et al, 2018), the relief plays a key role in pedodiversity, since along the slopes, there may be mixtures of parent materials, conditioning the formation of soil with peculiar properties. It is possible to find the occurrence of Nitossolos distinct from those previously studied in other regions of Brazil (Cooper and Vidal-Torrado, 2000;Ferreira et al, 2003;Silva et al, 2009;Melo et al, 2010) The southern coastal region of Pernambuco, in addition to the estuarine environments, is formed by the Atlantic forest ecosystem, the natural vegetation of which is practically nonexistent.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the presence of minerals such as kaolinite, goethite, illite, and quartz in the clay fraction of all soils profiles ( Figure 3) and low values T (Table 3), indicating the neoformation was an important process. This soil mineralogy demonstrates the influence of the humid tropical climate for the genesis of soils with a high degree of weathering, which generally uniformizes the mineralogy of the clay fraction along the slope, as described by Neves et al (2018) and Brilhante et al (2017) on the south coast of Pernambuco. This also highlights the importance of management that increases the contribution of the organic matter to the exchange complex of these soils (Stevenson, 1994).…”
Section: Discussionmentioning
confidence: 68%
“…The formation of goethite in these soils would be product of the alteration of ferromagnesian minerals (Buol and Weed, 1991), such as amphiboles and biotite present in granite, which exhibit strong alteration in tropical climate (Buol and Weed, 1991). Brilhante et al (2017) demonstrated that the formation of goethite in rhyolite-derived soils under similar climatic conditions was derived of mafic minerals and primary oxides, associated with changes in the pedogenetic environment, more favorable to the maintenance of moisture in the soils.…”
Section: Discussionmentioning
confidence: 98%
“…A acidez influencia diretamente o potencial produtivo dos solos brasileiros (SILVA et al, 2018), pois estes são caracteristicamente representados por soluções ácidas, isto é, o alto teor de íons de hidrogênio livres (H+) conferindo aos mesmos pH baixos (BRILHANTE et al, 2017), podendo ser intensificado por práticas e produtos aplicados durante o cultivo e manejo do solo. Segundo Gomes (2020) essa condição ácida pode limitar o desenvolvimento radicular das plantas, reduzindo sua capacidade de absorção de água e nutrientes, desfavorecendo a produção agrícola brasileira.…”
Section: Introductionunclassified